LAMOTRIGINE USE IN THE TREATMENT OF EPILEPSY IN ELDERLY PATIENTS - S. R. Nurmuhametova; R. V. Magzhanov (Эпилепсия и пароксизмальные состояния, 2016)
Abstract: epilepsy is 3d common neurologic problem after cerebrovascular diseases and dementia in elderly patients. At the onset of epilepsy in elderly patients the most frequent etiologic factors are cerebrovascular, neurodegenerativ diseases, neurosurgical pathology. About 25 % of epilepsy cases in elderly patients are related to idiopathic epilepsy. In elderly people all type of seizures can be observed. In the international recommend ations on the treatment of elderly patients with focal seizures gabapentin, lamotrigine, carbamazepine are used. Lamotrigine is used as first line therapy of epilepsy in elderly patients in monotherapy or combined drug therapy.